Cultural Self-Awareness Training in OBGYN Residency. (October 2017) - Lutz, Elizabeth; Riley, Rachel; Bouldin, Sheila; Hueppchen, Nancy
Abstract : OBJECTIVE: Develop and implement a training session for our OBGYN department that expands knowledge of one's own culture and fosters an awareness of the cultures of colleagues. METHODS: Needs Assessment including review of the 2014 ACGME Annual Resident Survey, which highlighted need for improved respect in the workplace. This prompted a meeting of the Designated Institutional Officer with the faculty of the OBGYN department regarding improved communication and sensitivity. An extended cultural competency curriculum was suggested from this meeting. Discussions with the institutional Director for Inclusion and Diversity Strategy confirmed that policies of inclusion and diversity are reviewed at new resident orientation; however, there is no further formal training for residents.Focus Group conducted with graduating residents to discuss their experiences during residency regarding issues of respect in the workplace and cultural sensitivity.Developed Framework for curriculum. Workshop conducted to address the specific objectives: Increase knowledge concerning cultural awareness and cultural competency; Identify personal attitudes regarding culturally sensitive issues and biases; Develop skills for addressing culturally sensitive issues. EVALUATION: Pre- and posttests developed with the Office of Diversity and Inclusion to assess knowledge, attitudes, and beliefs. Twenty-one residents and faculty attended the workshop. Nineteen of 21 (90%) of participants felt more open to learning of others' cultures and beliefs after this activity, and 18/21 (86%) felt closer to their colleagues after this activity. DISSEMINATION: Present to local "Ed Talks" conference, which promotes Educational Scholarship across the institution. Submit to MedEdPortal. REFLECTIVE CRITIQUE: The workshop was very well-received by those in attendance.